Islamicity Financial Performance Index in Indonesian Islamic Banks - Dita Andraeny; Dessy Diana Putri (Shirkah: Journal of Economics and Business, 2017)
This study aims to critically analyze the effect of islamic social reporting, intellectual capital  and  the  sharia supervisory board on islamicity financial performance index of Islamic Banks in Indonesia during 2011-2015. The samples of this study are ten islamic commercial banks that were initially selected by using purposive sampling method. Islamicity financial performance index was used as a measure of financial performance of Islamic  banks  which are consist of profit sharing ratio, zakat performance ratio, equitable distribution ratio, and islamic income versus non islamic income ratio. The analysis technique performed in this study is partial least squares. The results of this research revealed that islamic social reporting, intellectual capital and sharia supervisory board have positive and significant effect on islamicity financial performance index of Islamic  banks.Keywords: islamic social reporting, intellectual capital, sharia supervisory board, islamicity financial performance index